Thermal degradation behaviour of resins in aluminium composite under isothermal condition. (August 2017) - Zhu, Guoliang; Wang, Wei; Wang, Rui; Xiao, Yanping; Yang, Yongxiang; Dong, Anping; Wang, Donghong; Shu, Da; Wang, Jun; Sun, Baode; Boom, Rob
Abstract: As a member of the aluminium composite, GLARE (GLAss fibre/epoxy REinforced aluminium laminates) was used in the upper fuselage of Airbus A380 because of its superior mechanical properties over monolithic aluminium alloys. Thermal processing is a potential method for materials recycling and reuse from GLARE scrap with the aim of environmental protection and economic benefits. Thermal delamination is a crucial pre-treatment step for GLARE recycling. Differential scanning calorimetry (DSC) and Thermogravimetric analysis (TGA) tests have been used to identify the decomposition temperature range of epoxy resins under non-isothermal condition in our previous work [1]. To obtain an appropriate solution for GLARE thermal delamination, the thermal degradation behaviour of epoxy resins in GLARE under isothermal conditions were investigated and isothermal decomposition kinetic models were built up based on DSC and thermogravimetric analysis TGA. The thermal delamination process of GLARE is determined based on thermal analysis results and experimental optimization.